Experimental study on the dynamic behavior of rubber concrete under compression considering earthquake magnitude strain rate - Li, Furong; Wu, Yongyi; Xie, Xinghua; Zhao, Kai; Yu, Zhenpeng (Journal of Civil Engineering and Management, 2020)
To examine the compressive dynamic performance of rubber concrete, a uniaxial compression experimental study on rubber concrete was carried out using a hydraulic servo based on five different rubber substitution rates under eight different earthquake magnitude loading strain rates. The compressive failure modes and stress-strain curves of rubber concrete were obtained. By comparatively analyzing the mechanical characteristics of rubber concrete under different loading conditions, the following conclusions are drawn: with the increase in rubber substitution rate, the integrity of concrete upon compressive failure is gradually improved, and rubber particles exhibit an evident modification effect on cement mortar at the concrete interface. Under the influence of loading strain rate, the patterns of compressive failure mode of rubber concrete with different substitution rates are similar to that of ordinary concrete. Under the same loading strain rate, with the increase in rubber substitution rate, the compressive strength of rubber concrete gradually decreases while the plastic deformation capacity gradually increases. For the same rubber substitution rate, the compressive strength and elastic modulus of rubber concrete gradually increases with the increase in loading strain rate. The increase in rubber substitution rate gradually reduces the increasing amplitude of compressive strength and elastic modulus of rubber concrete under the influence of loading strain rate. Meanwhile, an equation was proposed to describe the coupling effect of rubber substitution rate and strain rate on the compressive strength dynamic increase factor of rubber concrete, and the underlying stress mechanism was further discussed. These results have significance in promoting the application of rubber concrete in engineering practice.